Plurilingual expatriate teachers at the university: a 'Français Langue Etrangère' case in Italy. Issue 3 (3rd July 2019) - Zanola, Maria Teresa
ABSTRACT: The article aims at analysing the role of plurilingual expatriate teachers: in fact, the topic of the dynamics of cooperation between native and non-native speaker teachers of foreign languages is empirically investigated in relation to French as a Foreign Language ( Français Langue Etrangère – FLE). Learners' needs will be then considered, along with their training from intermediate to upper intermediate levels and native and non-native speaker teachers' attitudes. The discussion will focus on the advantages of a balanced cooperation between the two profiles of teachers, insofar as its advantages seem to outweigh its drawbacks. The article highlights the importance of creating mixed teams of teachers to the maximum benefit of students and their preparation, both for exams and their future professional needs by analysing the case of the organisation of FLE teaching at a university language centre over the 2008–2018 decade.